Recent Advances on Hepatitis C Virus in Dialysis Population - Fabrizio Fabrizi; Piergiorgio Messa; Paul Martin (Karger Publishers, 2014)
Hepatitis C virus (HCV) infection remains common among patients undergoing regular dialysis and good evidence supports the detrimental role of HCV on survival in patients undergoing maintenance dialysis. According to an updated meta-analysis of clinical studies (n=15; 195,370 unique patients on maintenance dialysis), the summary estimate for adjusted relative risk (all-cause mortality) with anti-HCV across the published studies was 1.32 with a 95% Confidence Intervals of 1.24; 1.42, homogeneity assumption was not rejected. Various mechanisms support the excess death risk of HCV-infected patients on regular dialysis, in addition to liver disease-related mortality. The adjusted relative risk for cardiovascular mortality among HCV-infected patients on regular dialysis was 1.26 (95% Confidence Intervals, 1.10; 1.45); the increased cardiovascular mortality in anti-HCV positive patients has been associated in part to malnutrition and chronic inflammation. The current standard of care for HCV in dialysis population is combined antiviral therapy (pegylated interferon plus ribavirin) with a rate of viral response of around 60%. Triple therapy with telaprevir proved to be effective and safe in dialysis patients with HCV but only anecdotal evidence exists. Antiviral treatment of HCV-infected patients on maintenance dialysis could lead to cure the liver damage and the extrahepatic complications. The future availability of all-oral interferon/ribavirin free regimens for antiviral treatment of HCV will help nephrologists to improve survival in this high-risk group.